Item-specific control of attention in the Stroop task: Contingency learning is not the whole story in the item-specific proportion-congruent effect. - Spinelli, Giacomo; Lupker, Stephen J. (Memory & Cognition, 2020)
A robust finding in the Stroop literature is that congruency effects (i.e., the color-naming latency difference between color words presented in incongruent vs. congruent colors) are larger for color words presented most often in their congruent color than for color words presented most often in incongruent colors. However, the cause of this item-specific proportion congruent (ISPC) effect is unclear, as it might be produced by either a conflict-adaptation strategy (e.g., prepare for conflict when the word RED appears) and/or a more general learning mechanism of stimulus-response contingencies (e.g., prepare to respond blue when the word RED appears). Thus far, attempts to directly dissociate the two processes appear to indicate no role for conflict adaptation, at least in situations in which contingency learning is also possible. We re-examined this conclusion in a Stroop task in which contingency learning and item-specific conflict frequency were manipulated partially independently. In addition to a contingency-learning effect emerging for stimuli matched on conflict frequency, a conflict-adaptation effect also emerged for stimuli matched on contingency. The two effects also had different time courses, with the contingency-learning effect emerging early and remaining stable throughout the experiment and the conflict-adaptation effect arising later in the experiment. These results challenge not only the contingency-learning account of the ISPC effect, an account that denies the existence of a conflict-adaptation process, but also control accounts that assume that, although conflict-adaptation processes do exist, they are not used when contingency learning is also possible.